Optimisation of methods of diagnosis and correction of heel foot in children with cerebral palsy - O.A. Danylov; O.V. Shulha (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
The main cause of heel foot is muscle imbalance due to dysfunction of the triceps femoris muscle. Literature data indicate the need to study issues related to changes in the anatomy and function of the foot flexor muscles and calcaneus and to determine indications for optimal methods of correction of heel foot. Purpose - to study the anatomical and functional changes in the calf muscle and bones in children with heel foot to determine the optimal methods of diagnosis and correction of deformity. Materials and methods. We analysed the results obtained during the treatment of 14 patients (28 cases) aged 11 to 17 years with cerebral palsy complicated by calcaneal foot formation. Two groups were formed: the main group of 6 patients (12 cases), in which posterior calcaneal osteotomy with Achilles tendon plasty and transposition of the tibialis anterior tendon was performed; the comparison group of 8 patients (16 cases), in which only soft tissue surgery was performed. The comparative group was divided into 2 subgroups, which differed in radiological parameters of Bohler and Kite Danilov angles: the subgroup A - 3 patients (6 cases), the subgroup B - 5 patients (10 cases). Clinical and radiological methods were used to examine patients. Results. The structure and shape of the calcaneus change in the presence of heel foot, which leads to changes in the Danilov angle and the angles between the trabecular lines. Correction of the shape of the calcaneus is a prerequisite for creating optimal biomechanical gait conditions. Transplantation of the tibialis anterior tendon eliminates the pathological effect of its retraction; achilloplasty eliminates the functional deficiency of the triceps tendon. Conclusions. The results of surgical correction on soft tissues showed effectiveness at Bohler, Kite <35⁰, Danilov <40⁰ angles. At higher values, it is necessary to supplement the intervention with a posterior calcaneal osteotomy. The study was conducted in accordance with the principles of the Declaration of Helsinki. The study protocol was approved by the local ethics committees of all institutions participating in the study. Informed consent was obtained from the patients. No conflict of interests was declared by the authors.